Rough Sets and Knowledge Technology [electronic resource] : Second International Conference, RSKT 2007, Toronto, Canada, May 14-16, 2007: Proceedings - RSKT 2007 (2007 : Toronto, Ont.); Yao, JingTao; SpringerLink (Online service) (Berlin Heidelberg : Springer-Verlag GmbH., 2007)
PSZJBL